2015
DOI: 10.1159/000430918
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Knowledge and Attitudes towards Cancer Peer Support Programs

Abstract: The objective of this study was to gain a better understanding of cancer patients' preexisting knowledge, expectations and concerns towards peer support programs. Data were collected and analyzed in 51 patients using a standardized short interview and content analysis. Only 37% of the patients claimed to know peer support programs, and half of these regularly attended a support group. Forty-seven percent of the patients who did not know these programs showed a general interest. Reasons for attending a support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
0
13
0
4
Order By: Relevance
“…In this regard, MPs differed from other cancer patients , almost half of whom reported that they made use of these facilities. There are several causes of low use, but the main reason seems to be inadequate public awareness of the scope and availability of support options .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, MPs differed from other cancer patients , almost half of whom reported that they made use of these facilities. There are several causes of low use, but the main reason seems to be inadequate public awareness of the scope and availability of support options .…”
Section: Discussionmentioning
confidence: 99%
“…There are several causes of low use, but the main reason seems to be inadequate public awareness of the scope and availability of support options [ 29,30 ] .…”
Section: First: Personal Consultations Continue To Be the Primary Ir mentioning
confidence: 99%
“…Most studies examining barriers to participation have focused on traditional face‐to‐face models. These studies have identified low rates of referrals from health professionals, the regular time commitment, scheduling difficulties, travel constraints, feeling unwell, distress at seeing others' health declining, and feeling uncomfortable speaking in a group format as barriers to participation …”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified low rates of referrals from health professionals, the regular time commitment, scheduling difficulties, travel constraints, feeling unwell, distress at seeing others' health declining, and feeling uncomfortable speaking in a group format as barriers to participation. [14][15][16] The internet presents individuals with new choices for accessing peer support. Web-based peer support includes email groups, chat rooms, online forums, and social networking.…”
mentioning
confidence: 99%
“…In dieser Hinsicht unterschieden sich die MP von anderen Krebspatienten , von denen fast die Hälfte angab, dass sie diese Angebote nutzten. Für die geringe Nutzung sind verschiedene Gründe denkbar, der wichtigste scheint jedoch eine generelle mangelnde öffentliche Wahrnehmung der Verfügbarkeit und des Umfangs von Unterstützungsmöglichkeiten zu sein .…”
Section: Diskussionunclassified